STUDY ON THE CHANGE OF THE INTERNAL WAVE AMPLITUDES IN A DISPLACEMENT PROCESS IN THE VIETNAMESE WATERS - Xuan, Nguyen Ba; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2008)
In this paper some results of calculating and predicting a displacement of the internal wave amplitudes on basis of using the method of solving the equations of the Eigenvalues and Modes of the internal wave are presented. The results show that: the internal waves always displace in space and time with the amplitudes changed.fi-om I m to 35m. The internal waves in the study region have a tendency of increasing the average amplitudes with the depth and reach the maximum values in the layers of 250m, 350m and 450m.